Modified external fixation technique for treatment of distal radial metaphyseal-diaphyseal junction fractures in pediatric patients - Zhu, Huanye; Gao, Chao; Wang, Mengyao; Zhang, Nan; Cao, Jin (Frontiers in Pediatrics, 2025)
BackgroundDistal radius metaphyseal-diaphyseal junction (DRMDJ) fractures in children are often unstable and frequently require surgical intervention. Although various clinical approaches are available, each has its limitations. We introduced a modified external fixation technique for managing pediatric DRMDJ fractures. This study aimed to evaluate the clinical efficacy of this technique.MethodsBetween June 2021 to June 2024, a total of 57 pediatric patients with DRMDJ fractures were reviewed retrospectively. All patients were managed using a modified external fixation technique that incorporated distraction closed reduction and fixation, thereby facilitating early functional recovery without the need for cast immobilization. Postoperative follow-up was conducted at scheduled intervals and included radiographic evaluation (x-rays), assessment of wrist function scores, and recording of patient satisfaction metrics.ResultsSuccessful closed reduction and application of external fixation were achieved in all 57 pediatric patients. Throughout the follow-up period, no cases of nonunion or fixation failure were observed. The treatment protocol facilitated early functional rehabilitation, as evidenced by a progressive and statistically significant improvement in Cooney scores: from 74.5 ± 10.7 at 3 weeks to 87.5 ± 7.2 at 6 weeks, 93.5 ± 4.5 at 3 months, and 96.8 ± 2.7 by 6 months postoperatively (p < 0.05). Postoperative surveys indicated high rates of satisfaction among patients and their families.ConclusionThe modified external fixation technique for pediatric DRMDJ fractures enables early functional rehabilitation and a quicker return to school activities, while obviating the need for secondary hardware removal surgery. This approach adheres to minimally invasive principles and cosmetic acceptability, positioning it as an effective therapeutic strategy for treating pediatric DRMDJ fractures.